Pengaruh Independensi Komite Audit Dalam Memoderasi Karakteristik Chief Executive Officer Terhadap Kualitas Pelaporan Keuangan - Kelly, Kelly; Mardianto, Mardianto (Universitas Gorontalo, 2023)
This study aims to examine how audit committee independence moderates’ CEO characteristics on financial reporting quality in companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. The research sample consisted of 1945 data collected through a purposive sampling method. Research was performed using panel regression and processed by Eviews10 software using a quantitative approach to statistical data. This study concluded that audit committee independence is able to moderate the relationship between CEO tenure and real earnings management with a negative coefficient on financial reporting quality, howecer was unable to moderate the relationship of CEO expertise and CEO ownership.